MXene/polypyrrole coated melamine-foam for efficient interfacial evaporation and photodegradation - Mu, Xiaotong; Chen, Lihua; Qu, Nannan; Yu, Jiale; Jiang, Xiaoqian; Xiao, Chaohu; Luo, Xingping; Hasi, Qimeige (Journal of colloid and interface science, 2023)
[Display omitted] •An MXene/polypyrrole coated melamine-foam (MF-MXene/PPy) was successfully fabricated.•The π-π interaction between PPy and MXene effectively inhibits the rapid recombination of electron-hole pairs.•The MF-MXene/PPy demonstrates high efficiency for water evaporation and pollutant degradation.•The MF-MXene/PPy showed salt tolerance and salt collection during evaporation.•The superior activity is attributed to the synergy of photothermal and photocatalysis effect. The application of photothermal materials in seawater desalination, wastewater treatment have been widely studied, however, there are relatively few studies that combine photothermal effects and solar-driven photocatalysis and exhibit efficient solar-driven water evaporation performance and excellent photocatalytic ability. Form the perspective of practical application, it is of great significance to combine photothermal effect with solar-driven photocatalysis to develop environment-friendly evaporator with low cost, simple preparation process and ability of seawater desalination, wastewater treatment and photodegradation of organic dyes. In this paper, a novel multifunctional MXene/polypyrrole (PPy) coated melamine foam (MF) named as MF-MXene/PPy was successfully prepared by simple impregnation and in-situ polymerization. The MF-MXene/PPy has rich porosity (89.13 %), abundant water molecule transport channels, excellent light absorption capacity (about 94 %), low thermal conductivity (0.1047 W m−1 K−1), and exhibits excellent performance in solar desalination, wastewater purification and photodegradation of organic dyes. Under 1 kW m−2 illuminate, the solar energy conversion rate and efficiency of MF-MXene/PPy reaches up to 1.5174 kg m-2h−1 and 91.24 %. Moreover, due to the regular pore size of MF-MXene/PPy, good salinity tolerance was shown even after continuous evaporation in 20 wt% NaCl for 8 h. After continuous evaporation in 70 mL of 20 wt% NaCl for 8 h, the amount of salt collected could reach 0.2 g. In addition, MF-MXene/PPy also possessed excellent visible light degradation ability for organic dyes, and the degradation rate of methylene blue (MB), rhodamine B (RHB) and methyl orange (MO) were 92.38 %, 88.92 % and 91.75 %, respectively. As a fundamental research, this research will open a novel way to the development of new evaporator.